2020
DOI: 10.3390/bs10120189
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning, Life Satisfaction, and Their Relationship with the Financial Attitudes of Older Individuals Who Participate in an Active Aging Program

Abstract: Life expectancy has increased in many countries throughout the world over recent years, leading to new challenges related to aging. A large part of the population is over 60 years old, and therefore studies that focus on financial autonomy and active aging are necessary. In this paper, we analyze the relationship between cognitive functioning and life satisfaction in relation to financial attitudes in a sample of 251 elderly adults (71% women) participating in an active aging program (M = 67.5, SD = 4.5). We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Nevertheless, several scholarly works predominantly conceptualize it as the ultimate phase within an individual's life cycle, distinguished by a diminished capacity to adjust to one's surroundings effectively. To clarify, aging encompasses a range of biological, social, psychological, and cultural transformations resulting in various outcomes, such as increased reliance on others, reduced cognitive flexibility, and challenges adjusting to a dynamic environment (Idárraga-Cabrera et al, 2020). The policy framework put forth by the World Health Organization (WHO) encompasses the concept of active aging, a constructive process aimed at maximizing health, engagement, and safety to improve individuals' overall quality of life as they age (Martin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several scholarly works predominantly conceptualize it as the ultimate phase within an individual's life cycle, distinguished by a diminished capacity to adjust to one's surroundings effectively. To clarify, aging encompasses a range of biological, social, psychological, and cultural transformations resulting in various outcomes, such as increased reliance on others, reduced cognitive flexibility, and challenges adjusting to a dynamic environment (Idárraga-Cabrera et al, 2020). The policy framework put forth by the World Health Organization (WHO) encompasses the concept of active aging, a constructive process aimed at maximizing health, engagement, and safety to improve individuals' overall quality of life as they age (Martin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As China's population ages, active aging is becoming more important [1]. Numerous studies have shown that cognitive ability declines with age, which in turn accelerates the aging of older individuals and affects their independence [2][3][4][5][6][7]. When cognitive decline reaches a certain level, pathological changes may even occur, leading to an increased prevalence of cognitive dysfunction and diseases such as Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%